The Indian public sphere : readings in media history - Aravind Rajagopal(Editor) (Themes in politics, 2009)
"Part of the Themes in Politics series, this volume examines the emergence of the Indian public sphere and its interplay with politics, society, and culture. It surveys a wide range of communication media contributing to this development--oral, print, radio, television, cinema, and the Internet--through an analysis of the transition from the colonial to the postcolonial period. The essays in this volume show that mediation is a social process that extends beyond 'the media' and must be understood as a component of historical dynamics. They explore a wide range of historical and political mediations--from the use of the drum and buffalo horn as instruments of peasant insurgency against the British, and early Hindi pulp fiction, to socio-political implications of advertising, Hindu tele-epics, saas-bahu serials and the Internet. Identifying the continuities and changes in media from an interdisciplinary perspective, the essays are organized into four themes--the formation of a colonial public sphere; the emergence of a national popular domain; transformations in national developmentalism; and emergent orders such as consumerism and digital culture. A comprehensive introduction provides an understanding of Indian media through the analytical framework of the public sphere." -- Book jacket.